Providing an Environmental Audit Model for Improving Sustainable Development - Rostami, Mohammad Ali; Mahmoodi, Mohammad; Mohaghegh, Arefeh (Business, Marketing, and Finance Open, 2024)
The purpose of environmental auditing is to evaluate the environmental impacts of organizational and corporate activities with an emphasis on compliance with environmental laws, regulations, and standards. Environmental auditing can help organizations assess their performance in environmental protection and propose recommendations for improving sustainable environmental performance. Therefore, the aim of the present study is to review the literature and develop a framework in the field of environmental auditing and present a model for monitoring executive organizations. In this research, a qualitative approach using grounded theory was employed. A purposive sampling method was used, and semi-structured interviews were conducted with 14 experts. Identifying the pattern and ranking the main components of environmental auditing for monitoring executive organizations from the perspective of audit type was the main objective of this study. The results of the research led to the development of an environmental audit model, consisting of causal factors including appropriate environmental policymaking, the development of environmental auditing standards, and intervening factors such as the high cost of environmental destruction, the international importance of environmental issues, and contextual factors involving environmental crises, environmental culture, environmental technology. The interactive dimension includes issues such as environmental disclosure, efficiency in resource usage, and the preservation of environmental sustainability, while the consequential dimension includes improvement in achieving sustainable development through environmental auditing.